Examining the Most Severe Logistics and Supply Chain Issues Experienced by Malaysian SMEs - Nik Ab Halim Nik Abdullah; Sabariah Yaakub; Muhammad Subhan (International Journal of Supply Chain Management, 2018)
Literature revealed that both the internal and external factors may result in business failure among Small and Medium Size Enterprise (SME). One of the external factors identified is non-availability or deficiency in logistics and supply chain operations. Thus, this study was conducted with the objective to identify the most severe logistics and supply chain issues faced by SMEs in Malaysia. Quantitative research design was employed, where data were collected through mail survey questionnaire. The frequency of respondents selecting 4 (Severe) and 5 (Very severe) for each survey item were calculated, in order to determine which issues are the most severe among Malaysian SMEs. The items are then ranked based on the highest number of respondents selecting 4 and 5. It provides more meaningful information on the most severe logistics and supply chain issues faced by SMEs, if compared to analysing the mean score of each item as the mean value may be distorted by high standard deviation. Findings indicate that difficulties and inaccuracies in forecasting inventory top the list, followed by inability to fulfil orders due to inventory shortages and keeping wrong mix of inventories. Thus, it can be concluded that inventory related issues are the most critical problems faced by Malaysian SMEs. This study contributes towards logistics and supply chain management literature as it provides an in depth information on the logistics and supply chain related issues faced by SMEs. For practitioners and the relevant government agency, this study sheds light on the most severe issues so that firms and government agency can focus their efforts on rectifying these severe logistics and supply chain issues